Prevention of infection in external fixator pin sites. - Jennison, T; McNally, M; Pandit, H (Elsevier, 2014)
Infection in external fixator pins is known to be a significant problem, with incidences between 3% and 80% reported in the literature. An infection occurs when planktonic bacteria adhere to external fixator pins and subsequently produce a biofilm which protects the bacteria from host defences. The most commonly implicated organisms are Staphylococcus aureus and Staphylococcus epidermidis. Once an infection occurs, treatment is difficult. Systemic antibiotics have limited benefits and considerable side-effects. The only definitive management is removal of the pin. This review will consider the current and potential future strategies for reducing pin site infection. Techniques to prevent infection must prevent bacterial adhesion, allow good osteointegration and have a low toxicity. Current areas of interest reviewed are titanium-copper alloys, nanosilver coatings, nitric oxide coatings, chitosan coatings, chlorhexidine and iodine, hydroxyapatite and antibiotic coatings. At present there is no consensus on the prevention of pin site infection, and there is a paucity of randomized controlled trials on which to draw a conclusion. Whilst a number of these strategies have potential future use, many of the above strategies need further studies in animal models to ensure no cytotoxicity and prevention of osteointegration. Following this, well-designed randomized controlled clinical trials are required to give future ways to prevent external fixator pin site infections.